Problems of innovative policy development of the region in modern conditions in the Republic of Belarus - S. Komarova (State University of Management, 2020)
A new approach to assessing the competitive position of the region in the field of innovation and investment development has been proposed, which allows you to take into account a number of new indicators that most fully reflect the situation in the development of the region. As a result of the study of existing approaches to assessing the competitive position of the region, it has been revealed that some indicators are of a low informative nature and do not fully reflect the region’s innovation and investment policy.The methodology used to assess competitiveness is currently quite conservative, and the indicator of the volume of manufactured products (goods, works, services) does not generally reflect the innovative development of the region. In assessing the competitiveness of the region according to this methodology, there is no important component that speaks of the innovative development of the region, this is an investment climate and innovation policy that is inherent in a given business entity. Therefore, a modern approach to the selection of indicators that most fully reflect innovation activityand investment climatehas been offered in the article.As a novelty, it has been proposed to assess the innovation climate in the region, exploring a number of new parameters, such as research costs, research organizations and the number of innovation-active organizations involved in technological innovation, export of goods and services. Due to the fact that these indicators have different units of measurement (quantitative and cost), it has been offered to use the Harrington method as an approach, which, recalculating the indicators through a dimensionless scale, makes it easy to find a comprehensive indicator of competitiveness. A new approach in calculating a comprehensive indicator of competitiveness to assess the investment and innovation position of the region also has been proposed.